2004
DOI: 10.1108/01604950410564492
|View full text |Cite
|
Sign up to set email alerts
|

How economists cite literature: citation analysis of two core Pakistani economic journals

Abstract: Selected volumes of the Pakistan Development Review (PDR) and the Pakistan Economic and Social Review (PESR) were analysed to find the citation pattern of their articles. Eight volumes of each journal were selected, two volumes representing a decade. The results revealed that the PDR has been the most cited journal. The mean score of citations per article remained insignificantly different in the two core journals. More than 50 per cent of the citations from both journals were single-authored. More than 50 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The highlights of a few prominent ones are “healthcare service quality” (SQ) (Valencia-Arias et al , 2018), SQ of “travel agencies” (Chen et al , 2016), genesis of SQ research (Pereira et al , 2013) and “perceived quality of internet services” (Duque Oliva et al , 2006). Similarly, the literature survey highlights such works in various domains like “economics” (Sharif and Mahmood, 2004), “E-Marketing” (He, 2012) “medical science” (Ullah et al , 2008), agriculture (Majid, 2000), “carbapenem resistance” (Sweileh et al , 2016), “carbon market research” (Du et al , 2015), “organic chemistry” (Kumari, 2009; Kumari, 2006), “alternative energy research” (Mao et al , 2015), “medicinal chemistry” (Rivera et al , 2010; Soboleva and Evdokimenkova, 2018), “analytical chemistry” (Arkhipov and Berezkin, 2002), “nanotechnology” (Ganaie and Wani, 2021), the “fuzzy sets theory field” (Cobo et al , 2011), “fluorochemistry” (Bouznik and Zibareva, 2015), “surfactant chemistry” (Bailon-Moreno et al , 2005) and “catalysis” (Zibareva and Parmon, 2013; Zibareva et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The highlights of a few prominent ones are “healthcare service quality” (SQ) (Valencia-Arias et al , 2018), SQ of “travel agencies” (Chen et al , 2016), genesis of SQ research (Pereira et al , 2013) and “perceived quality of internet services” (Duque Oliva et al , 2006). Similarly, the literature survey highlights such works in various domains like “economics” (Sharif and Mahmood, 2004), “E-Marketing” (He, 2012) “medical science” (Ullah et al , 2008), agriculture (Majid, 2000), “carbapenem resistance” (Sweileh et al , 2016), “carbon market research” (Du et al , 2015), “organic chemistry” (Kumari, 2009; Kumari, 2006), “alternative energy research” (Mao et al , 2015), “medicinal chemistry” (Rivera et al , 2010; Soboleva and Evdokimenkova, 2018), “analytical chemistry” (Arkhipov and Berezkin, 2002), “nanotechnology” (Ganaie and Wani, 2021), the “fuzzy sets theory field” (Cobo et al , 2011), “fluorochemistry” (Bouznik and Zibareva, 2015), “surfactant chemistry” (Bailon-Moreno et al , 2005) and “catalysis” (Zibareva and Parmon, 2013; Zibareva et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given recent research undertaken by the authors on Pakistani LIS scholars' profiles in RG (Ali and Richardson, 2017) and given the generally poor impact of Pakistani researchers in terms of citations (Ali and Richardson, 2016, p. 1;Ashraf Sharif and Mahmood, 2004), the authors were interested in whether there was a correlation between how well HEIs ranked nationally and/or internationally in terms of their research, and how well these same institutions ranked in RG.…”
Section: Research Objectivesmentioning
confidence: 99%
“…Haridasan and Kulshrestha [74] found that the cited half-life of the literature in information science journal Knowledge Organization is 14 years. The mean age of citations for two economics journals, namely Pakistani Development Review and Pakistan Economic and Social Review was 9.16 and 12.96 respectively [75].…”
Section: Age Of Citations and Publication Half-lifementioning
confidence: 99%